PEMBERDAYAAN KELOMPOK TANI SIDO MAKMUR TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT - Solda Azvika; Andi Warisno (UNISAN JURNAL, 2022)
Community empowerment of farmer groups is very important to encourage, motivate, and strengthen their economic potential. The purpose of this study was to determine the level of community welfare through farmer group empowerment in an Islamic economic perspective.This research includes field research (field research). The method used in this research is qualitative data analysis with descriptive nature of the research. The results showed that the implementation of community empowerment for the prosperous Sido farmer group towards improving the welfare of the community in Sidoharjo Village through counseling programs and skills training. The implementation of community empowerment of the prosperous Sido farmer group in Sidoharjo Village can be said to be successful, the members admitted that there was an increase in knowledge and skills in agriculture, obtained new information about agriculture, there was an increase in income before they joined and after joining the prosperous Sido farmer group, and they were very enthusiastic about the empowerment program. This means that the empowerment of the Sido prosperous farmer group community has a positive effect in improving the welfare of the Sido prosperous farmer group members in Sidoharjo Village, Jati Agung District, South Lampung Regency and the Sido prosperous farmer group member community can already be said to be a prosperous society. Empowerment in the view of Islamic Economics is seen from the principles of Islamic Economics that community empowerment for members of the prosperous Sido farmer group is in accordance with the rules or limitations in Islam that have been determined by Allah SWT in order to achieve falah in the world and in the hereafter and for welfare. the community members of the prosperous Sido farmer group are in accordance with welfare in the view of Islamic Economics.